Essential and risk elements in horses affect haematology, serum biochemistry and oxidative status parameters - Marko Halo; Róbert Kirchner; Filip Tirpák; Tomáš Slanina; Katarína Tokárová; Anton Kováčik; Michal Miškeje; Agnieszka Greń; Grzegorz Formicki; Marko Halo; Roberto Madeddu; Peter Massányi (Scientific Reports)
Abstract The abundance of chemical elements in the blood of horses can indicate the physiological balance, health of animal as well as can be taken as an indicator of environmental pollution. The aim of this work was to analyse haematological, biochemical parameters, TOS, FRAP, SOD, Gpx, TAS and their correlations with concentrations of essential and risk elements in blood of horses stabled in two different locations: The National Stud Farm Topoľčianky (n = 11; 11 stallions, consisting of the breeds 6 Lipizzan, 3 Slovak warmblood, 2 Holsteiner) and Experimental Centre at Institute of Animal Husbandry, SUA in Nitra (n = 10; 4 stallions, 5 geldings, 1 mare, 4 stallions, 5 geldings and 1 mare, consisting of the breeds 3 Slovak warmblood, 4 Czech warmblood, 3 Holsteiner). Blood samples were obtained from horses (n = 21) from two localities in the Slovak Republic during May. The haematological profiles of horses from both locations were within reference values. The values of biochemical parameters of horse samples that underwent analysis showed only minor deviations from the referential values reported by several authors. Fe was the most accumulated elements (383.95 mg/L and 403.61 mg/L, respectively). Finally, this investigation based on correlation analyses identified essential and risk elements in horse blood serum and significant negative correlation between Cd and GRA, HGB and HCT was observed in The National Stud Farm Topoľčianky and a positive correlation was recorded between Zn and total proteins in the Experimental Centre at Institute of Animal Husbandry, SUA Nitra. The obtained data could be used as a control indicator to identify risk hazards related to the heavy metals in relation to the health of animals.